The Characterization and Optimization of an Underwater Gamma-Ray Detection System (DUGS) - Jacques Bezuidenhout; Rikus R. le Roux; Kennedy K. Kilel (Journal of Marine Science and Engineering, 2023)
Sedimentation can cause numerous problems in rivers, estuaries, harbors, and coastal areas. It is therefore important to trace and model the movement of sediments. The natural physical, chemical, and biological components of the aquatic sediment generally relate to these features in its terrestrial catchment area. It consequently contains the naturally occurring radionuclides of thorium, uranium, and potassium, which can be used as tracers. To achieve this aim, a delta underwater gamma system (DUGS) was developed to map the radionuclides in aquatic sediments. Though the system has been tested for radiometric accuracy, the low concentrations of natural radionuclides in aquatic sediments and the attenuation by the water and detector enclosure necessitated an evaluation to determine the detection efficiency of the detector along with optimal operational parameters. These included spectra accumulation time and underwater speed. The DUGS was consequently used to determine and optimize these parameters for mobile measurement of aquatic sediments. The acquired gamma spectra were also analyzed using full spectrum and energy window analysis to determine the optimal method for extracting the activity concentrations of the nuclides in the sediments.